Associations between family communication, perceived stress, and resilience with life satisfaction among UPM pre-university students - Pour, Manoochehr Taghi; Ismail, Asmah; Wan Jaafar, Wan Marzuki; Rajabi, Gholamreza (Department Of Surgery, Mayo Hospital, 2021)
Background: Alfred W. Adler (1870-1937), psychotherapist and founder of the school of individual psychology, believed that education, marriage, and job play important role in human development. Higher learning is a demanding and challenging period for students that can result in high rates of psychological distress affecting their life satisfaction. Aim: The research is to study the links between family communications, perceived stress and resilience with life satisfaction among pre-university students in UPM. Method: A cross-sectional study was conducted among a sample of 310 (females 158 and 152 males) preuniversity students from a public university in Malaysia. Four instruments were used in this research namely the Family Communication Scale (FCS, Olson et al., 2004), Perceived Stress Scale (PSS, Cohen et al., 1983) Resilience Scale (CD-RISC, Connor-Davidson, 2003) & The Satisfaction with Life Scale (Diener et al. 1985). The data were analyzed using independent t-test, Pearson correlation coefficients and multiple regressions. Results: The finding of this study revealed that there are simple and multiple relationships between family communications, perceived stress and resilience with life satisfaction among pre-university students. Conclusion: The research may guide university counselors to view adolescents’ life satisfaction holistically and assist them in developing preventive and intervention plans for the university new enrolled students. Also, the results will provide students with some knowledge on their life satisfaction and its effects on their future accomplishments.